2019
DOI: 10.1107/s2053229619004327
|View full text |Cite
|
Sign up to set email alerts
|

The rich crystal chemistry of theAMM′(PO4)2morphotropic series: NaZnAl(PO4)2, the first Na representative with a new structure type

Abstract: A novel phosphate, sodium zinc aluminium bis(phosphate), NaZnAl(PO 4 ) 2 , was obtained under mild-temperature hydrothermal conditions at 553 K. The crystal structure has been studied using single-crystal X-ray experimental data. The pseudo-hexagonal phase NaZnAl(PO 4 ) 2 crystallizes in the monoclinic space group P2 1 /c. Its unique crystal structure is based on a three-dimensional (3D) framework built by Zn-, Al-and P-centred tetrahedra sharing vertices. Channels parallel to the [101] and [101] directions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…5(a)]. The minerals celsian, BaAl 2 Si 2 O 8 (Griffen & Ribbe, 1976), and filatovite, K(Al,Zn) 2 [(As,Si)O 4 ] 2 (Filatov et al, 2004), crystallize in the same structure type, as do a large group of phosphates with first-row transition metals and Al (Yakubovich et al, 2019). The structural feature of the isotypic natural and synthetic compounds of this family is the close topology of their cationic substructures to that of feldspars with the characteristic design of a 'crosslinked Jacob's ladder' (Taylor, 1933) (Fig.…”
Section: Crystal Structure Of K(almentioning
confidence: 99%
See 1 more Smart Citation
“…5(a)]. The minerals celsian, BaAl 2 Si 2 O 8 (Griffen & Ribbe, 1976), and filatovite, K(Al,Zn) 2 [(As,Si)O 4 ] 2 (Filatov et al, 2004), crystallize in the same structure type, as do a large group of phosphates with first-row transition metals and Al (Yakubovich et al, 2019). The structural feature of the isotypic natural and synthetic compounds of this family is the close topology of their cationic substructures to that of feldspars with the characteristic design of a 'crosslinked Jacob's ladder' (Taylor, 1933) (Fig.…”
Section: Crystal Structure Of K(almentioning
confidence: 99%
“…Recently, we have analysed the crystal chemical diversity of isoformula phosphates AMM 0 [PO 4 ] 2 (A + = Na, K, Rb, NH 4 , M 2+ = Cu, Ni, Co, Fe, Zn, M 03+ = Fe, Al, Ga), including 18 representatives (Yakubovich et al, 2019). It has been shown that the rich crystal chemistry of the discussed morphotropic series (seven structure types) is due to the possibility of different coordination of M and M 0 atoms in the oxygen environment, from tetrahedral to octahedral, including five vertices, as well as to the size of alkali metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…The KCuAl(PO4)2 [15] and RbCuAl(PO4)2 [16] compounds exhibit 3D structures formed by CuO6 octahedrons sharing a common edge to form zigzag chains connected to a AlO5 polyhedron and PO4 tetrahedrons through corners and an edge. The compounds KCoAl(PO4)2 [17], NH4(Al,Co)2(PO4)2 [18], KZnAl(PO4)2 and β-NaZnAl(PO4)2 [19], (NH4)0,83(Zn0,83Al1,17)(PO4)2 [20] and α-NaZnAl(PO4)2 [21] adopted a 3D structural framework formed entirely by tetrahedrons.…”
Section: Introductionmentioning
confidence: 99%